PERSPEKTIF MASYARAKAT MUSLIM TERHADAP TRADISI BOREH DALAM RESEPSI PERNIKAHAN (Studi Kasus Desa Pulo Kec. Ciruas Kab. Serang) - Nurul Hikam; Masrokhin Masrokhin (JOURNAL SAINS STUDENT RESEARCH, 2024)
The tradition of the Boreh tribe is the custom of processions (a procession with many people). This performance invites participation from many groups such as family, friends and colleagues. Accompanied by traditional music as a means of introduction. There are various types of beehives used in traditional beehive construction, research findings. In this research, the method used is an empirical juridical approach; However, data collection techniques include observation, questionnaires and documentation. The data analysis technique used is inductive analysis. From the research results, it can be concluded that in the Boreh tradition, there are two main beliefs: belief in Allah SWT and also in the spirits of ancestors or ancestors. However, from the perspective of Islamic law, this tradition is considered inappropriate because it involves the use of offerings. However, from a customary law perspective, Boreh is considered part of the customs of the people of Pulo Village, where the majority of the population is Muslim. Based on 'Urf's analysis, the Boreh tradition can be considered contrary to the principles of Islamic law, even though it has aspects of benefits and harms. Benefits include the belief that praying according to Islamic law can bring longevity. However, the harm lies in the use of offerings which can be misleading, and the belief that not carrying out the Boreh tradition can cause death, both for the wife and husband.